If biodiversity offsets are a dead end for conservation, what is the live wire? A response to Apostolopoulou & Adams. Issue 1 (18th October 2016) - Dempsey, Jessica; Collard, Rosemary-Claire
Abstract : Ecofeminist Maria Mies describes capitalist social relations as an iceberg. The visible tip represents the formal economy, where capitalist value emerges from exploited waged labourers and the circulation of monetized goods and assets. Underneath the waterline lurks the rest of the iceberg, and its size dwarfs the tip. Here, Mies points to a much larger world of exploitation on which commodity production and profit-making depend: women, colonies and, at the very base, nature. The bodies, places and materials of the submerged, invisible iceberg supply unwaged labour and unpriced inputs and energies that are productive; capitalism depends on this deeply undervalued work. Let us restate: capitalism exploits, yes, but strangely, it is a mode of organizing society that also relies on this exploitation. As Mies ([1986]1998, p. 200) writes, 'the exploitation of colonies, as well as that of women and other non-wage workers, is absolutely crucial to the capitalist accumulation process'; this exploitation 'constitutes the eternal basis for capitalist accumulation' (Mies, 2007, p. 269).